Novel Phenotypes and Cardiac Involvement Associated With DNA2 Genetic Variants - González-del Angel, Ariadna; Bisciglia, Michela; Vargas-Cañas, Steven; Fernandez-Valverde, Francisca; Kazakova, Ekaterina; Escobar, Rosa Elena; Romero, Norma B.; Jardel, Claude; Rucheton, Benoit; Stojkovic, Tanya; Malfatti, Edoardo (Frontiers in Neurology, 2019)
Objectives To report two novel DNA2 gene mutations causing early onset myopathy with cardiac involvement and late onset mitochondriopathy with rhabdomyolysis. Methods We performed detailed clinical, muscle histopathology and molecular studies including mitochondrial gene NGS analysis in two patients (Patient 1 and Patient 2), a mother and her son, belonging to a Mexican family, and a third sporadic French patient. Results Patient 1 and 2 presented with an early onset myopathy associated with ptosis, velopharyngeal weakness and cardiac involvement. Patient 3 presented rhabdomyolysis unmasking a mitochondrial disease characterized by a sensorineural hearing loss, ptosis and lipomas. Muscle biopsies performed in all patients showed variable mitochondrial alterations. Patient 3 had multiple mtDNA deletion in his muscle. Genetic studies revealed a novel heterozygous frameshift mutation in DNA2 gene (c.2346delT p.Phe782Leufs*3) in P1 and P2, and a novel heterozygous missense mutation in DNA2 gene (c.578T>C p.Leu193Ser) in the P3. Conclusions To date only few AD cases presenting either missense or truncating DNA2 variants have been reported. None of them presented with a cardiac involvement or rhabdomyolysis. Here we enlarge the genetic and phenotypic spectrum of DNA2-related mitochondrial disorders.